Mission, Vision, and Value Appropriation: A Correlational Analysis - Contreras-Pacheco, Orlando E.; Pirazán Parra, Alejandra; Villarreal Pinzón, Maira (Cuadernos de Administración, 2022)
The present study discusses the effective functionality of mission and vision statements in a business environment. In this spirit, the study evaluates the potential association between these two strategic elements and the achievement of organizational results, especially in terms of the competitive capacity of a company. Particularly, the study formulates a conceptual approach to determine the potential incidence of a mission and a vision statement’s quality on the organizational levels of value appropriation. Subsequently, using structural equation modeling through partial least squares, this approach is evaluated on a sample of 120 large companies registered in the Department of Santander, Colombia. The findings suggest that, although there is a positive association between a good mission and a good vision, the value appropriation only seems to depend on the former and not on the latter. The study validates that an adequately constructed mission statement could become a powerful mechanism for the sake of formulating and implementing strategies. Additionally, it states that the ability to build a quality mission is related to the company’s ability to create appropriate value and therefore, be competitive.